Early Contrast Enhancement: A novel magnetic resonance imaging biomarker of pleural malignancy. (April 2018) - Tsim, Selina; Humphreys, Catherine A.; Cowell, Gordon W.; Stobo, David B.; Noble, Colin; Woodward, Rosemary; Kelly, Caroline A.; Alexander, Laura; Foster, John E.; Dick, Craig; Blyth, Kevin G.
Highlights: A novel MRI biomarker of pleural malignancy is described – Early Contrast Enhancement. Early Contrast Enhancement is a semi-objective, perfusion-based biomarker. Early Contrast Enhancement can be measured in patients with minimal pleural thickening. Abstract: Introduction: Pleural Malignancy (PM) is often occult on subjective radiological assessment. We sought to define a novel, semi-objective Magnetic Resonance Imaging (MRI) biomarker of PM, targeted to increased tumour microvessel density (MVD) and applicable to minimal pleural thickening. Materials and methods: 60 consecutive patients with suspected PM underwent contrast-enhanced 3-T MRI then pleural biopsy. In 58/60, parietal pleura signal intensity (SI) was measured in multiple regions of interest (ROI) at multiple time-points, generating ROI SI/time curves and Mean SI gradient (MSIG: SI increment/time). The diagnostic performance of Early Contrast Enhancement (ECE; which was defined as a SI peak in at least one ROI at or before 4.5 min) was compared with subjective MRI and Computed Tomography (CT) morphology results. MSIG was correlated against tumour MVD (based on Factor VIII immunostain) in 31 patients with Mesothelioma. Results: 71% (41/58) patients had PM. Pleural thickening was <10 mm in 49/58 (84%). ECE sensitivity was 83% (95% CI 61–94%), specificity 83% (95% CI 68–91%), positive predictive value 68% (95% CI 47–84%), negative predictive value 92% (78–97%). ECE performance was similar or superior to subjective CT and MRI. MSIG correlated with MVD (r = 0.4258, p = .02). Discussion: ECE is a semi-objective, perfusion-based biomarker of PM, measurable in minimal pleural thickening. Further studies are warranted.